Identifikasi Kromatografi Lapis Tipis Sudamala (Artemisia vulgaris L.) - Ira Arundina; Theresia Indah Budhy S.; Muhammad Luthfi; Retno Indrawati (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
Identification of Sudamala (Artemisia vulgaris L.) Thin Layer Chromatography. Oral squamous cell carcinoma is the type of cancer which is most frequently found in oral cavity. The primary risk factor of malignancy in oral cavity includes the habit of consuming tobacco and or alcohol. The plant sudamala (Artemisia vulgaris L.) is often used in the community as anti-tumor in digestive organ, including in oral cavity. However, there have been no studies on active ingredients playing the role as anti-cancer in oral cavity. The species are mostly from the genus Artemisia, while those generally growing in Indonesia are the species Artemisia vulgaris L. The objective of this study is to explain the identification by TLC of sudamala. The study was sudamala extraction, identification of sudamala extract, sudamala fractionation with Vacuum Column Chromatography and identification of sudamala fractionation with TLC (Thin Layer Chromatography). The result shows that the fractionation using hexane extract resulted in 11 fractions of n-hexane: ethyl acetate. The conclusion of this study is that the fraction of n-hexane: ethyl acetate (3:7, v/v) sudamala (Artemisia vulgaris L.) identified contains terpenoids compounds.